Phase I Studies of Acebilustat: Biomarker Response and Safety in Patients with Cystic Fibrosis. Issue 1 (2nd November 2016) - Elborn, JS; Horsley, A; MacGregor, G; Bilton, D; Grosswald, R; Ahuja, S; Springman, EB
Abstract : There is a significant unmet need for safe and effective anti‐inflammatory treatment for cystic fibrosis. The aim of this study was to evaluate the safety of acebilustat, a leukotriene A4 hydrolase inhibitor, and its effect on inflammation biomarkers in patients with cystic fibrosis. Seventeen patients with mild to moderate cystic fibrosis were enrolled and randomized into groups receiving placebo or doses of 50 mg or 100 mg acebilustat administered orally, once daily for 15 days. Sputum neutrophil counts were reduced by 65% over baseline values in patients treated with 100 mg acebilustat. A modestly significant 58% reduction vs. placebo in sputum elastase was observed with acebilustat treatment. Favorable trends were observed for reduction of serum C‐reactive protein and sputum neutrophil DNA in acebilustat‐treated patients. No changes in pulmonary function were observed. Acebilustat was safe and well tolerated. The results of this study support further clinical development of acebilustat for treatment of cystic fibrosis.